Determination of Leaders in Education Management - Muhamad Toyib; Ahmad Syukri; Kasful Anwar Us (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
This article aims to describe the determination of leaders in education management. Library studies are conducted to explore a variety of relevant sources. The resources used came from reputable books and journals. The sources were searched and searched according to their intended purpose. Methods used to collect research data in the form of literature data that have been selected, searched, presented, and analyzed. The source of this research data looks for library data whose substance blinds the act of processing philosophically and theoretically. The data analysis techniques in the form of content analysis. The results of the library study revealed that the determination of leaders in education management includes the motivation of the work of leaders consisting of intentions, taqwa, and sincere; hard work; sincerity; confidence, and good quality of working life. A good leader is a leader who can perform his role and functions properly with a strong determination with measurable parameters. The results revealed the influence of leadership in education management.